Proceedings of the Ocean Drilling Program 1993
DOI: 10.2973/odp.proc.sr.132.302.1993
|View full text |Cite
|
Sign up to set email alerts
|

Shatsky Rise: Seismic Stratigraphy and Sedimentary Record of Pacific Paleoceanography since the Early Cretaceous

Abstract: Shatsky Rise consists of three highs arranged in a linear trend more than 1300 km long. Shatsky Plateau, the southernmost and largest of three highs is represented by an exposed basement high of presumed Late Jurassic age flanked by a sedimentary sequence of at least Cretaceous and Cenozoic age that reaches a maximum thickness of more than 1100 m. Drilling on Shatsky Rise is restricted to eight DSDP and ODP sites on the southern plateau that partially penetrated the sedimentary sequence. Leg 132 seismic profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…several times thicker (Den et al, 1969;Gettrust et al, 1980). Furthermore, seismic profiling showed that the tops of the rise edifices hold thick piles of pelagic sediments (up to 1.2 km), whereas sediments on the rise flanks are thin or occasionally absent (Ewing et al, 1966;Ludwig and Houtz, 1979;Neprohnov et al, 1984;Sliter and Brown, 1993).…”
Section: Prior Research On Shatsky Risementioning
confidence: 94%
“…several times thicker (Den et al, 1969;Gettrust et al, 1980). Furthermore, seismic profiling showed that the tops of the rise edifices hold thick piles of pelagic sediments (up to 1.2 km), whereas sediments on the rise flanks are thin or occasionally absent (Ewing et al, 1966;Ludwig and Houtz, 1979;Neprohnov et al, 1984;Sliter and Brown, 1993).…”
Section: Prior Research On Shatsky Risementioning
confidence: 94%
“…In contrast, option A would require quite variable sedimentation rates and periods of condensation, which would suggest that the Permanente Quarry record of OAE1a is incomplete. Condensation and hiatuses at about the Barremian-Aptian boundary have been identifi ed at other Pacifi c sites (Sliter, 1989(Sliter, , 1992Sliter and Brown, 1993), but it is not clear if these horizons can be correlated on a basinal scale. On the southern high of Shatsky Rise, the most signifi cant hiatus appears to occur near the Barremian-Aptian boundary, but it is likely below the interval of OAE1a (see Figure 7 in Sliter and Brown, 1993).…”
Section: Implications For Early Aptian Paleoceanographymentioning
confidence: 99%
“…Second, the spreading of the ridges adjacent to Shatsky Rise was relatively rapid, and the rise volcanism was spread laterally, rather than stacked vertically, so that the history of the rise is more easily interpreted. Third, sediments on Shatsky Rise flanks are generally thin [ Ewing et al , 1966; Ludwig and Houtz , 1979; Sliter and Brown , 1993], so the morphology of the rise, which can be measured by bathymetry, is a direct reflection of its structure and evolution. Finally, the rapidly spreading triple junction indicates the formation of Shatsky Rise on thin lithosphere, which should have had minimal influence on melt generation and migration.…”
Section: Introductionmentioning
confidence: 99%